Labor Migration of The Population and Evaluation of Supply Chain on the Labor Market - Abdurakhmanov, Kalandar Khodzhaevich; Madorbekovich Mukhitdinov, Erkin; Ivanovich Grishin, Viktor; Kalandarovna Abdurakhmanova, Gulnora; Faizullaevich Kuchkarov, Gaybullo (ExcelingTech, 2019)
The article considers internal and external labor migration and supply chain effects in the process of forming the internal labor market in the Republic of Uzbekistan. The quantitative and qualitative composition of labor resources is identified in conjunction with other factors determining the pace of the country’s economic development, the level of the population welfare and the overall economic potential of the socio-economic system as a whole are determined. Within this context, scientific research in the field of organized labor migration and its impact on employment, formation of basic concepts characterizing migration processes, and the development of a new migration policy seem relevant. Economic transformations associated with the development of new forms of ownership, labor relations, the emergence of new socially vulnerable segments of the population in the republic suggest the improvement of the state employment policy. To that end, it is advisable to develop and use more advanced forms and methods for regulating labor migration of the population, including within the republic. The considered positive and negative consequences of the labor import impact on the economy of the receiving state mainly indicate the systematic nature of labor migration and its complexity for scientific analysis. Certain short term positive effects can give an impetus to negative trends in the long-term, which dictates the need for government management by migration processes, aiming to maximize the positive effects and minimize costs.